New sacred architecture - Richardson, Phyllis (Laurence King, 2004)
This timely book reflects an awakening of interest in religious faiths and the emergence of a global exchange of architecture and culture. While Spain's Rafael Moneo has recently completed a cathedral in Los Angeles, Britain's Thomas Heatherwick is designing a Buddhist temple in Japan, John Pawson is working on a Cistercian monastery in the Czech Republic and Richard Meier has completed his Jubilee Church in Rome. It seems, as one Wallpaper (registered) pundit commented, religion is getting a redesign and the architect's faith is as unimportant as his or her nationality.